Evaluate the Application of the Occupational Health and Safety Management System Based on International Standard (ISO 45001: 2018) :A Case Study in the Iraqi Ministry of Education - Sura Abdu Lateef Fadhil Alshaheen (Journal of Techniques)
This research aims to measure the level of application of the international standard for the occupational health and safety management system (ISO 45001: 2018) in educational institutions by determining the size of the gap between the actual reality of occupational health and safety and the requirements of the researched standard, as well as proposing steps to implement the standard. Researching educational institutions in the Ministry of Education office, and the check list was adopted as a main tool for data collection by using statistical methods to obtain the results of the research represented (by the arithmetic mean and percentage to determine the extent of conformity and the actual size of the gap). The research reached a number of conclusions, the most prominent of which was that The procedures and requirements of the occupational health and safety management system came in very weak rates, as the percentage reached (15%) with a gap of (85%), and this gap came as a result of not adopting the application of the occupational health and safety standard.